Numerical solution of the inverse induction logging problem for thin-layered sections ("grouse"-type) - Myrontsov, M.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
The features of a numerical solution of the inverse unstable problem for the electrometry of oil and gas wells for thin-layered sections ("grouse"-type) are considered. It is shown that the created and developed algorithm for the four-probe induction low-frequency logging allows one to solve the inverse problem.